Automated water level monitoring system in open water - Ya. I. Lepikh; Yu. Ya. Bunyakova; Yu. V. Kryshnev; P.O. Snegur (Геофизический журнал, 2019)
The article is devoted to the creation of automated systems for monitoring the level of water in open waters, intended primarily to control and prevent floods during natural phenomena. The existing at this time control systems are based on outdated principles and technical means and do not allow timely assessment of the real flooding catastrophic danger.